Dampak kepercayaan, kualitas layanan dan ketersediaan informasi dalam menimbulkan minat mahasiswa memanfaatkan Perpustakaan IAIN Tulungagung - Endang Rifngati (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2019)
This research is motivated by the fact that the tendency of students to have lack of interest in utilizing the IAIN Tulungagung library. This can be seem from the uncertain visitor’s library statistics, where visitor statistics show an increase at the beginning of the new school year but it will decrease when entering the even semester. Of course there are many factors that cause student interest to use the library. The focus of the research in this paper is as follows; (1) How does the impact of trust in generating students’ interest to take advantage of the IAIN Tulungagung library?; (2) How is the impact of service quality in generating students’ interest in utilizing the IAIN Tulungagung library?; (3) What is the impact of the availability of information in generating students’ interest in utilizing the IAIN Tulungagung library?. This type of research was qualitative research. In this study the data collection techniques used were the observation, interviews and documentation in order to obtain data, while the data analysis used data presentation and conclusion drawing. The research found that for the impact of trust could increase students’ interest in utilizing the library from the aspect of integrity. Whereas in terms of service quality that could give an impact in generating student interest utilizing the library was from the aspect of tangibles (physical evidence) and from the aspect of emphaty. As for the impact of the availability of information that could increase student interest in utilizing the Tulungagung IAIN library were convenience and relevant aspects.